The μDrop Method Enhances Melanin Content Measurement in the in vitro Melanogenesis Model Using B16F10 Cell Line - Yuliarni, Dinda; Kamilah, Mutiara Mila; Nugraha, Gaga Irawan; Faridah, Lia; Bashari, Muhammad Hasan; Ekawardhani, Savira (Cell and BioPharmaceutical Institute, 2025)
Background: The B16F10 cell line is a cell frequently used in melanin content assays. However, reports on cell models using B16F10 are limited, particularly as the robust model cell in the Indonesian cosmetics industry. We found measuring melanin content using microplate spectrophotometry to be challenging, so this research was conducted to develop a method using μDrop spectrophotometry.Materials and methods: In this in vitro study, the B16F10 melanoma cell line was cultured in Roswell Park Memorial Institute (RPMI) medium containing 5% fetal bovine serum (FBS). The cells were categorized into control, stimulated, and treated groups. Melanogenesis stimulation was achieved using 1μM α-melanocyte-stimulating hormone (α-MSH), while inhibition using 800 μg/ml kojic acid. After treatment, the cells were incubated for 48 hours. Their melanin content was then measured using an ELISA reader with a μDrop method and compared with the microplate method. Statistical analysis used a one-way ANOVA test with Turkey’s Post Hoc analysis.Results: The μDrop method increased the melanin signal into the linear range of machine readings, while the signals from the microplate method fell far below this range. The B16F10 melanoma cell lines stimulated by α-MSH exhibited increased melanin production compared with the control group, while kojic acid treatment significantly reduced (p<0.05) melanin content in the stimulated group.Conclusion: The μDrop method significantly outperformed the microplate method in measuring melanin content within melanogenesis cell models, offering enhanced accuracy and particularly excelling at quantifying low content of melanin. Keywords: μDrop, microplate, melanin, melanogenesis, B16F10 cell line, RPMI